Does whole-body vibration acutely improve power performance via increased short latency stretch reflex response? - Alexandre Fernandes, I.; Kawchuk, G.; Bhambhani, Y.; Chagas Gomes, P. S. (Journal of Science and Medicine in Sport, 2013)
Objectives: It remains unclear whether an increased intrafusal mechanical sensitivity is related to the vibration-induced performance improvement. This investigation aimed to determine the residual acute effect of whole-body vibration and its duration on pre-activation levels, short-latency stretch reflex and performance during drop jumps. Design: Repeated measures. Methods: Eleven amateur athletes performed a set of three 45 cm-drop jumps before and during a 20 min-interval following three randomized conditions: No, Low (30 Hz, 5 mm) and High vibration (45 Hz, 5 mm). Ground reaction force peak, Soleus and Vastus Lateralis short latency stretch reflex onset and amplitude were assessed during drop jumps. Results: A significant effect for time revealed an immediate drop jump height increase after High vibration. A longer contact time also followed High vibration while no changes were detected after Low vibration. Vibration did not affect ground reaction force peak and short latency stretch reflex component. Conclusions: High vibration constituted an intervention for improving performance although there was no evidence of increased stretch reflex responses.